Elastic properties of liquid crystals - Zbigniew Raszewski; Stanisław Kłosowicz; Jerzy Zieliński; Rafał Mazur (Biuletyn Wojskowej Akademii Technicznej)
The paper presents elastic properties of liquid crystals, especially their nematic phase. Anoutline of a development of theories describing these properties is given. The model describing liquidcrystal as continuous medium is formulated. The curvature theory of elasticity of nematic liquidcrystals based on Zocher – Oseen – Frank’s approach is discussed in details. In this way, essentialelastic properties of nematics as well their relative material parameters are described.Keywords: liquid crystals, nematics, elastic properties, deformations, continuous medium